Constitutional dysfunction on trial : Congressional lawsuits and the separation of powers - Farrier, Jasmine, 1970- (Cornell University Press, 2019)
"Farrier argues that U.S. political dysfunction is attributable to a permanent imbalance of power among the branches of government that transcends party alignments and political moods. She looks at a class of extra-legislative actions that challenges this imbalance and aims to restore proper functioning in the Madisonian system of checks and balances"--